The Role of Public Service Motivation in Enhancing Job Performance: A Study of College Counselors in China - Ming Guan (Education Sciences)
Public service motivation (PSM) plays a critical role in shaping the job performance of college counselors, whose responsibilities encompass both ideological-political education and student affairs management within Chinese higher education institutions. This study employs a large-scale survey and empirical analysis to explore the mechanisms linking PSM and job performance, focusing specifically on the mediating role of work engagement and the moderating effect of transformational leadership. A total of 550 college counselors from a diverse set of higher education institutions across China participated in the survey. The findings reveal that PSM significantly enhances job performance, with work engagement serving as a partial mediator in this relationship. Furthermore, transformational leadership positively moderates the influence of PSM and work engagement, thereby amplifying its indirect effect on job performance. These results contribute to the broader discourse on higher education management and offer practical insights for student affairs administrators aiming to optimize counselor performance and enhance institutional governance.